Implementation of Data Mining Using Naïve Bayes Classification Method To Predict Participation of Governor And Vocational Governor Selection In Jemirahan Village, Jabon District - Arif Senja Fitrani; Fajrillah Fajrillah; Wirda Novarika (STMIK Budi Darma, 2019)
General Election (ELECTION) is an important political event to determine a leader in a democratic country. The General Election (ELECTION) in East Java which was held on 27 June 2018 yesterday was the election of the Governor and Deputy Governor for the 2019-2024 period. There are two pairs of candidates for Governor and Deputy Governor. Through the General Election (ELECTION) then all parties can be accommodated what they want and aspire to so that a better life can be realized. The community is the determining component of the success or failure of an Election. Therefore, in this study the researcher wanted to examine how the electoral participation in Jemirahan Village, Jabon District by using the classification method, the Naïve Bayes algorithm. To predict the participation of the General Election (PEMILU) in Jemirahan Village, Jabon District, it can be done using the Naïve Bayes Algorithm with 6 predefined variables. The results of the prediction of election participation from the dataset taken were 300 data divided by 2, as many as 65% of 195 training data and 35% of 105 data testing.